2007
DOI: 10.1016/j.euje.2006.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Papillary fibroelastoma of the aortic valve: A rare cause of stroke

Abstract: We report a case of a 59-year-old woman with recurrent cerebrovascular insults caused by a papillary fibroelastoma of the aortic valve. Primary cardiac tumors are rare. Papillary fibroelastoma (PFE) is the most common valvular tumor and the second cardiac benign tumor after myxoma. The clinical presentation of PFE varies from asymptomatic to severe embolic complications. The tumor was surgically removed to avoid new embolic events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 6 publications
0
9
0
1
Order By: Relevance
“…8,9 The majority of these lesions are asymptomatic, although leftsided lesions are more likely to be symptomatic than rightsided lesions. 9,10 Symptoms associated with right-sided lesions may include right ventricular outflow obstruction, palpitations, weakness, and cyanosis. 9,10 Left-sided lesions tend to produce symptoms via embolization, either of the tumor itself or of thrombi attached to the tumor surface.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8,9 The majority of these lesions are asymptomatic, although leftsided lesions are more likely to be symptomatic than rightsided lesions. 9,10 Symptoms associated with right-sided lesions may include right ventricular outflow obstruction, palpitations, weakness, and cyanosis. 9,10 Left-sided lesions tend to produce symptoms via embolization, either of the tumor itself or of thrombi attached to the tumor surface.…”
Section: Discussionmentioning
confidence: 99%
“…9,10 Symptoms associated with right-sided lesions may include right ventricular outflow obstruction, palpitations, weakness, and cyanosis. 9,10 Left-sided lesions tend to produce symptoms via embolization, either of the tumor itself or of thrombi attached to the tumor surface. 9,10 Data regarding brain embolization rate are scant but one study done by Anastacio et al 11 showed that embolization to the brain was seen in 30% of the patients (n = 23) who underwent surgical resection of PFE.…”
Section: Discussionmentioning
confidence: 99%
“…Fibroelastom utgjør 6 %, men av de svulstene som opptrer på hjerteklaffer er imidlertid fibroelastom hyppigst (2). …”
Section: Sjøanemonesvulst 143unclassified
“…Magnetic resonance imaging yielded the same findings and allowed intracardiac thrombus formation as well as a vascularized tumor or metastasis to be ruled out. The patient was scheduled for surgery (tumor excision) because of the potential risk of embolization due to this tumor [4].…”
Section: Image Of the Monthmentioning
confidence: 99%
“…Magnetic resonance imaging yielded the same findings and allowed intracardiac thrombus formation as well as a vascularized tumor or metastasis to be ruled out. The patient was scheduled for surgery (tumor excision) because of the potential risk of embolization due to this tumor [4].A tumor size of 8×10 mm and an infiltration of the head of the anterior papillary muscle were found during surgery. Surgery was performed via right lateral minithoracotomy; intraoperatively a complete resection of the head of the papillary muscle had to be performed.…”
mentioning
confidence: 99%